The effects of technological innovations on the organizational structure and human resource development in selected academic libraries in the Philippines - Lapuz, Elvira B. (2003)
This study was conducted to determine the effects of technological innovations on academic libraries in the Philippines. Specifically, it sought to study how these innovations affect the formal organizational structure in the library. It also sought to determine the effects of these changes on human resource management. It further sought to determine the effects of these changes on the job requirements, tasks and functions of the library staff. Four academic libraries were included in the study. These are the Ateneo Professional Schools Library, the University of Asia and the Pacific Library, the De La Salle University Library and the Asian Institute of Management Library. A structured questionnaire was used to gather data on library staff opinions regarding the management of change brought about by the technological innovations in their respective libraries. The number of respondents totaled eighty-six (86). They were also asked to give their views regarding organizational structuring and how it affects the given tasks and functions. The respondents' training needs were also probed.